Lysophosphatidylcholine Increases Na+/Ca2+ Exchanger Expression via RhoB-Geranylgeranylation in H9c2 Cells - Sachiko Maeda; Kazuho Sakamoto; Isao Matsuoka; Takahiro Iwamoto; Junko Kimura (Elsevier, 2009)
The expression levels of the Na+/Ca2+ exchanger type 1 (NCX1) change under various cardiac pathophysiological conditions, but the mechanism is unknown. We previously demonstrated that lysophosphatidylcholine (LPC) increased NCX1 expression by activating RhoB in H9c2 cardiomyoblasts. Conversely, fluvastatin (Flv), a 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor, decreased NCX1 mRNA and protein expression by inhibiting RhoB. RhoB can be isoprenylated by either geranylgeranylpyrophosphate (GGPP) or farnesylpyrophosphate (FPP). Here we investigated which of GGPP or FPP is involved in the NCX1-increasing effect of LPC. When LPC was added with GGPP to the Flv-treated H9c2 cells, NCX1 mRNA was increased to a level significantly higher than that in the control cells. Only GGPP, but not FPP, allowed LPC to increase NCX1 mRNA in the presence of Flv. Furthermore, geranylgeranyltransferase 1 inhibitor (GGTI), but not farnesyltransferase inhibitor (FTI), inhibited the LPC-induced NCX1 mRNA increase. We conclude that geranylgeranylation, but not farnesylation, of RhoB mediates LPC-induced NCX1 mRNA increase in H9c2 cells. Keywords:: lysophosphatidylcholine, Na+/Ca2+ exchanger, H9c2 cell, RhoB, geranylgeranylation